A novel microbial-mineral preparation for the removal of offensive odors from poultry manure. (April 2017) - Borowski, Sebastian; Matusiak, Katarzyna; Powałowski, Szymon; Pielech-Przybylska, Katarzyna; Makowski, Krzysztof; Nowak, Adriana; Rosowski, Marcin; Komorowski, Piotr; Gutarowska, Beata
Abstract: This paper describes the research performed to develop a novel microbial preparation for deodorization of poultry manure. Three forms of the preparations were investigated: microorganisms ( Pseudomonas fluorescens, Enterococcus faecium, Bacillus subtilis, Bacillus megaterium, Leuconostoc mesenteroides and Lactobacillus plantarum ) on the mineral carrier (PBM), microbes in the form of spray-dried microcapsules (SDM) and freeze-dried powder (FDP). The experiments were performed in an installation consisting of four chambers, each with a working volume of 8 dm 3 . Each chamber was filled with a 0.5 kg of fresh poultry manure, onto which the tested preparations were sprinkled. The deodorization efficiency of the preparations was evaluated by passing air through the reactors and measuring odorants in the exhaust air. In the course of the experiments, the final formula of the preparation was established. It consisted of a perlite-bentonite mixture (20:80 by weight) as a sorbent, and mineral carrier to which 20% of SDM was added. The new preparation applied to poultry manure was particularly active against ammonia and hydrogen sulfide, which were reduced in the exhaust air by 94% and 60%, respectively, after 2 days of deodorization. The experiments also showed that the preparation can be stored for at least 5 months at both cooling (4 °C) and room (22 °C) temperatures with no decrease of its microbial activity. Highlights: Microbial-mineral preparations were tested for poultry manure deodorization. Encapsulates microbes mixed with perlite-bentonite was an optimal preparation form. Ammonia was reduced by the preparation by over 90%. The preparation revealed high stability during 5-months storage at 4 °C and 22 °C.